Mubarizati zahmatkishani kharij az mahdudah 1356 (Ittihadiyyahi-yi Danishjuyani Irani dar Amrika havadari "Sazmani Paykar dar Rahi Azadi-yi Tabaqahi-yi Kargar")
The struggles of the toilers in the shanty towns.